Is anti-theism incoherent? - Kahane, G (University of Illinois Press, 2021)
Anti-theists argue that the world, or our lives, would be overall worse if God exists because God’s existence imposes distinctive downsides. Many hold, however, that anti-theism is incoherent if we assume that God would not permit gratuitous evil to occur. This is because that would entail that any alleged downsides of God’s existence would be permitted only if they are necessary to bring about a greater good or to prevent an even greater evil. I will argue that this emerging consensus is mistaken: the argument from the principle of non-gratuitous evil to the falsity of anti-theism is invalid because it trades on an ambiguity. Appealing directly to God’s perfect goodness fails for similar reasons. Anti-theism can therefore only be rejected via substantive axiological debate.